Workability Behaviour of Powder Metallurgy Aluminium Composites. (1st July 2014) - Narayan, S.; Rajeshkannan, A.
Abstract : An efficient way to find the workability limit for powder metallurgy parts has been suggested. Compacts of Al-4%TiC, Al-4%WC, Al-4%Fe3 C, and Al-4%Mo2 C were produced to the relative density of 0.82 and 0.86 with three different geometries through primary operations of powder metallurgy routes. Each sintered compact was hot deformed to various strain levels till a visible crack appeared at the free surface. Oyane's fracture principle was used to develop a theory to study powder metallurgy compacts. A least square technique was used to determine the constants in fracture criteria and these equations were finally used to find workability limit. It is found that the projected technique was well in agreement with the experimental values.